The Influence of Internal Locus of Control on Academic Procrastination in High School Students - Prawitasari, Tiara; Suhendri, Suhendri (IKIP Siliwangi, 2024)
Academic procrastination is a problem often experienced by students. This research aims to determine the influence of internal locus of control on academic procrastination in class X students at SMA Negeri 9 Semarang. The research design used is ex post facto quantitative research. The study population was all first-grade students totaling 396 students. The research sample was taken with a simple random sampling technique totaling 180 students. The research instrument used a 20-item internal locus of control scale developed from Levenson’s theory (1981) and a 14-item academic procrastination scale developed from Ferrari’s theory (1995) theory. The data analysis technique uses descriptive analysis and simple linear regression analysis. The level of academic procrastination is in the high category (M = 49.15; SD = 5.78) and the level of internal locus of control is in the high category (M = 69.46’ SD = 8.174). Hypothesis testing shows that there is an influence of internal locus of control on academic procrastination (R2= 0.900, ρ < 0.05). This means that the internal locus of control contributes to academic procrastination by 90%, while the rest is influenced by other factors. Recommendations for future researchers can examine the role of internal locus of control on academic procrastination in terms of gender.